Controls of stable isotopes in precipitation on the central Tibetan Plateau: A seasonal perspective. (20th April 2019) - Zhang, Teng; Zhang, Yinsheng; Guo, Yanhong; Ma, Ning; Dai, Di; Song, Hongtao; Qu, Dongmei; Gao, Haifeng
Abstract: Determining the temporal controls on stable isotopes in precipitation is essential for the paleoclimate reconstruction and hydrological regimes in the Tibetan Plateau (TP). Although related studies have been conducted throughout most of the TP, conclusions for the central TP remain unclear. Therefore, in this study, we evaluated the climatic controls on precipitation isotopes on a seasonal basis using a 3-year (January 2014 to December 2016) dataset of daily precipitation isotopes from Xainza station in the Siling Co Basin of the central TP. Results showed that the precipitation δ 18 O displayed a distinct seasonal variation, with enriched values occurring in the pre-monsoon season and relatively depleted values in the monsoon season. Significant positive correlations between precipitation δ 18 O and temperature have been observed during the pre-monsoon and westerly seasons with short-distance moisture trajectories with a large percentage. In comparison, during the monsoon season, the strongest control was provided by integrated regional convections that occurred over several previous days (0–20 days). The increased transport distances extending to the humid ocean with enhanced upstream convections along the trajectory lead to more depleted isotopic values and thus the weakening of convections may be responsible for the increase of δ 18 O values during the post-monsoon season. Additionally, the comparison of d-excess values with other stations in the TP demonstrated the ever-present significant influence of continental moisture throughout the year. A slighter decrease in d-excess values during the monsoon season retained more signals of moisture evaporated from the continent and thus may lead us into more consideration of local recycles. These results indicated that the effects of different moisture sources, including the Indian monsoon and convections, should be considered when interpreting δ 18 O from the climate proxies and tracing the water cycles on the central TP.